Geodynamic and molecular characterization of endemic Cherax sp. in Wamena Dome, Papua, Indonesia - AGUS HARTOKO; DELIANIS PRINGGENIES; EDY. H.P. MELMAMBESSY; GERSON MANUEL; JOSAPHAT TETUKO SRI SUMANTYO; MUHAMMAD HELMI; HARIYADI HARIYADI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Hartoko A, Pringgenies D, Melmambessy EHP, Manuel G, Sumantyo JTS, Helmi M, Hariyadi H. 2025. Geodynamic and molecular characterization of endemic Cherax sp. in Wamena Dome, Papua, Indonesia. Biodiversitas 26: 4090-4102. Foreign aquarium demands threaten the high potential of Cherax sp. biodiversity in Papua. The new concept is the integration of geodynamic analysis and molecular characterization of Cherax sp. Spectral classification of DEM applied to reconstruct the collision of the Pacific and Australian tectonic plates to form Papua Island. The collision process generates the highland of the Wamena Dome, as well as formations of the northward and southward riverine systems. PCR gene amplification using a mitochondrial DNA-forward JgLCO1490 and reverse JgHCO2198 primers. DNA amplification using a PCR machine and Basic Local Alignment Search. Genetic distance analysis using matrix comparison to GenBank National Center for Biotechnology Information sequences. Phylogenetic tree generated using the Neighbor-Joining method with a bootstrap of 1,000 in MEGA-XII. Phylogenetic analysis of Cherax monticola from the Baliem River and Cherax quadricarinatus, as representatives of the Australian species, reveals that they belong to a single clade. The nearest genetic distance of C. monticola to the Australian origin of C. quadricarinatus is 0.17, and is high in C. monticola to C. preissi (0.234) and to C. doberai (1.4570). Most of the 30 Cherax sp. are found in the southward rivers of Papua. Haplotype network analysis has confirmed that C. monticola is the origin of Papua, and C. quadricarinatus is the origin of Australia. Tectonic plate geodynamic and DNA analysis confirming the origin of South Papua and Australia as previously one tectonic plate and induced Cherax sp. geographic endemicity.